Vielfalt begrüßen: ein rassismuskritischer Blick auf Jesus-Darstellungen in christlicher Kunst und Kinderbibeln - Keuchen, Marion (Die Bibel in der Kunst, 2024)
Despite increasing ethnic diversity in Germany, racist structures are still deeply rooted in society, as is demonstrated by various initiatives and studies. Racism is also evident in the depiction of Jesus Christ, who traditionally is portrayed as 'white' in Christian art, although he must be read biblically as a Person of Color (PoC). Examples such as the “Wales Window for Alabama” (1964) by Ronald John Petts and the contemporary icon by Kelly Latimore “Christ in The Rubble” (2023) show Jesus as PoC and address racism and social justice. Children’s Bibles continue to be dominated by ‘white’ depictions of Jesus and the people around him. Works such as the children’s Bibles by Desmond Tutu (lyrics) / Laure Fournier et al. (illustration) (2010), Sören Dalevi (lyrics) / Marcus-Gunnar Petterson (illustration) (2022), Willemijn de Weerd (lyrics) / Marieke ten Berge (illustration) (2022) and Andrea Karimé (lyrics) / Anna Lisicki-Hehn (illustration) (2023) offer more diverse and racism-sensitive depictions that contribute to the promotion of diversity competence and positive identity formation. The article argues for a more extensive representation of diversity in depictions of Jesus Christ in Christian art and children’s Bibles in order to avoid discriminatory stereotypes and to encourage PoC, children and adults.